Proceedings of the 2019 Ramazzini Days: Session III - The key characteristics approach to hazard identification - VV, AA (European Journal of Oncology and Environmental Health, 2019)
1. Introduction to the key characteristics approach Martyn Smith2. The key characteristics approach to hazard identification Martyn Smith3. Key characteristics of endocrine-disrupting chemicals Michele LaMerrill, USA4. Application of the key characteristics of carcinogens in IARC Monographs Kathryn Z. Guyton, France5. Key characteristics of bioactive chemicals Linda S. Birnbaum, USA6. Key Characteristics Approach to Organizing and Assessing Upstream Toxicity Information Lauren Zeise, USA